THE ORGANISATION OF TRANSPORT IN THE AGRIBUSINESS SECTOR IN THE RESEARCH OF THE FACULTY OF ECONOMIC SCIENCES OF WULS-SGGW IN THE 21ST CENTURY - Rokicki, Tomasz (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
Transport is a very important branch of the economy. It was quite well recognized in the case of industry services, however, there have been few studies on transport services provided in the agribusiness sector. This gap was filled by employees of the Faculty of Economic Sciences at WULS-SGGW. The subjects of interest were entities dealing in food processing. The study reviewed research and publications of the Faculty’s employees that were created in the 21st century. The majority of enterprises did not have a separate department dealing with transport. Apart from own transportation, small and micro enterprises also combined their own and external transport means. Forwarding services were used to a small extent in the shipping process organisation. The results of the research at WULS-SGGW and other studies were quite similar.